Digital Business and Marketing Training for Residents of RT 008 RW 010, Semper Barat Subdistrict, Cilincing District, North Jakarta - Tarmizi, Achmad; Damayanti, Ida Royani (Manunggal Halim Jaya, 2025)
This community service initiative aimed to strengthen digital marketing skills among residents of RT 008 RW 010, Semper Barat Subdistrict, North Jakarta. Many participants, mainly informal micro-entrepreneurs, had previously relied on conventional marketing methods and had minimal exposure to digital platforms. The training introduced them to tools such as Instagram, WhatsApp Business, Canva, and Shopee through a hands-on, participatory approach. Results showed significant improvements in digital literacy, content creation abilities, and confidence in promoting products online. Several participants successfully posted their products and received engagement from new customer segments. The program also fostered peer collaboration and addressed digital inclusion in underserved communities. While technical limitations such as device familiarity and internet access remained, the training demonstrated the potential of higher education institutions in supporting digital empowerment at the grassroots level